2016
DOI: 10.1002/jbio.201600062
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic single gold nanoparticle visualization by clinical intracoronary optical coherence tomography

Abstract: The potential use of Gold Nanoparticles (GNPs) as contrast agents for clinical intracoronary frequency domain Optical Coherence Tomography (OCT) is here explored. The OCT contrast enhancement caused by GNPs of different sizes and morphologies has been systematically investigated and correlated with their optical properties. Among the different GNPs commercially available with plasmon resonances close to the operating wavelength of intracoronary OCT (1.3 µm), Gold Nanoshells (GNSs) have provided the best OCT co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Recently, a study of dynamic single gold nanoparticle visualization by intracoronary OCT clearly demonstrated that AuNPs presence induced a relevant enhancement in the OCT contrast. This study showed that OCT signal has a linear increase with the backscattering cross section given by each AuNPs, which is highly dependent on the particular type of AuNPs used [25]. Hu and colleagues clearly demonstrated that, for the same concentration, gold nanoshells (multipolar plasmonic excitations in the 1000-1500 nm spectral range) present a higher contrast when compared to gold nanorods, showed by their extinction cross section values at OCT operating wavelength more than two orders of magnitude larger than gold nanorods, together with a reduced absorption efficiencies [25].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Recently, a study of dynamic single gold nanoparticle visualization by intracoronary OCT clearly demonstrated that AuNPs presence induced a relevant enhancement in the OCT contrast. This study showed that OCT signal has a linear increase with the backscattering cross section given by each AuNPs, which is highly dependent on the particular type of AuNPs used [25]. Hu and colleagues clearly demonstrated that, for the same concentration, gold nanoshells (multipolar plasmonic excitations in the 1000-1500 nm spectral range) present a higher contrast when compared to gold nanorods, showed by their extinction cross section values at OCT operating wavelength more than two orders of magnitude larger than gold nanorods, together with a reduced absorption efficiencies [25].…”
Section: Discussionmentioning
confidence: 80%
“…This study showed that OCT signal has a linear increase with the backscattering cross section given by each AuNPs, which is highly dependent on the particular type of AuNPs used [25]. Hu and colleagues clearly demonstrated that, for the same concentration, gold nanoshells (multipolar plasmonic excitations in the 1000-1500 nm spectral range) present a higher contrast when compared to gold nanorods, showed by their extinction cross section values at OCT operating wavelength more than two orders of magnitude larger than gold nanorods, together with a reduced absorption efficiencies [25]. With this study, it is now proved the potential ability of intravascular OCT for the detection on individual AuNPs in both static and non-static conditions and it opened new applications of this combination as real time evaluation of intravascular obstruction or pressure gradients.…”
Section: Discussionmentioning
confidence: 80%
“…Second, for metallic nanoparticles the backscattering is associated with the collective resonant excitations of charges (plasmon resonance overlaps with the IC‐OCT laser radiation). [1b,16] As a consequence, the backscattering cross section of, for instance, GNSs with enough plasmon resonance at OCT laser wavelength is as large as 0.7 × 10 −10 cm 2 per nanoparticle . The scattering cross section of IR‐QDs has not been reported up to now, but theoretical studies predict that the scattering cross section of individual QDs is much smaller than the absorption cross section .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, an adequate functionalization of these IC‐OCT contrast agents would lead to efficient accumulation in, for instance, atherosclerotic plaques or damaged endothelium, providing new diagnostic findings which would lead to personalized treatments. Up to now, only a number of gold nanoparticles (GNPs) have been demonstrated to be efficient contrast agents for IC‐OCT . Particularly, silica‐coated gold nanoshells with plasmon resonance close to the IC‐OCT laser wavelength (1.3 µm) and high backscattering cross sections were demonstrated as the best nanocontrast agents, showing significant IC‐OCT contrast enhancements in suspensions and tissues .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation